A new species of Metapelopia Silva, Oliveira & Trivinho-Strixino (Diptera: Chironomidae) from Peru - Dantas, Galileu P. S.; Hamada, Neusa; Araujo, Ana A. Huamantinco (Zootaxa, 2016)
A new species of the monotypic genus Metapelopia is described and illustrated based on all life stages. Adults of the Metapelopia peruensis sp. n. can be easily distinguished from those of M. corbii by the color pattern of the legs and abdomen. Larvae and pupae were collected associated with algae accumulated on rocks.